Hamburger : Clubmagazin von Girth&Mirth Deutschland. (Hamburg : Girth & Mirth Deutschland, 1995)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijksRedactie : Pf 302023, 20307 Hamburg
Duits
Periodiek